PHRASEOLOGICAL UNITS IN IBRAYIM YUSUPOV’S POETRY - Sabirbaeva Guljayna Saparbay qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Phraseological  units  represent  a  stable  and  culturally  significant  layer  of language that conveys figurative meaning rather than literal interpretation. In poetic discourse, such units function as semantic wholes and are understood through their contextual  and  oral  meaning.  This  article  investigates  phraseological  units, phraseological  unities,  and  phraseological  combinations  in  the  poetry  of  the Karakalpak poet Ibrayim Yusupov. The aim of the study is to analyze their semantic and stylistic functions without altering the original poetic lines. The research is based on  qualitative  linguistic  analysis,  where  phraseological  expressions  are  interpreted according to their figurative meaning. The findings demonstrate that Yusupov’s poetry reflects  national  phraseological  thinking  and  effectively  combines  traditional expressions  with philosophical  and  modern  concepts. This  study  contributes  to  the understanding of phraseology in Karakalpak poetic language within an international linguistic framework.